2022
DOI: 10.3390/su142114060
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact Modeling for a Small-Scale Field Test of Methane Removal by Iron Salt Aerosols

Abstract: Various authors have highlighted the possible removal of methane from the atmosphere via oxidation by broad releases of iron salt aerosols in order to serve climate protection goals. This technique is known as enhanced atmospheric methane oxidation (EAMO). This study proposes and employs a modeling approach for the potential environmental impacts associated with a hypothetical small-scale field test of EAMO consisting of seeding cargo-ship exhaust plumes with iron salt aerosols. Using a sample region in the So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…They observed a substantial reduction in CH 4 levels, with removal rates ranging from 46% (at 1.2 kg H 2 SO 4 ) to 96% (at 6.0 kg H 2 SO 4 ) and concluded that employing low-dose acidification proves to be a promising and viable strategy for mitigating CH 4 emissions [100]. Highly interesting ironsalt aerosol method, which is a mimic of natural reactions related to mineral dust particles, is capable of direct atmospheric CH 4 removal [101,102]. This method generates CH 4 depleting chlorine atoms in the tropospheric atmosphere, thereby capable of removing the total atmospheric CH 4 to some extent [103].…”
Section: Traditional Methods For Direct Atmospheric Methane Removalmentioning
confidence: 99%
“…They observed a substantial reduction in CH 4 levels, with removal rates ranging from 46% (at 1.2 kg H 2 SO 4 ) to 96% (at 6.0 kg H 2 SO 4 ) and concluded that employing low-dose acidification proves to be a promising and viable strategy for mitigating CH 4 emissions [100]. Highly interesting ironsalt aerosol method, which is a mimic of natural reactions related to mineral dust particles, is capable of direct atmospheric CH 4 removal [101,102]. This method generates CH 4 depleting chlorine atoms in the tropospheric atmosphere, thereby capable of removing the total atmospheric CH 4 to some extent [103].…”
Section: Traditional Methods For Direct Atmospheric Methane Removalmentioning
confidence: 99%